PENINGKATAN KOMUNIKASI INFORMASI AKUNTANSI MENGGUNAKAN GAMBAR KARTUN - Febrianto, Rahmat; Rafdinal, Rafdinal (Jurnal Akuntansi dan Keuangan Indonesia, 2006)
This research is aimed to answer how accounting information users classify accounting information when they are presented in different forms. Specifically, this research investigate whether users can efficiently and effectively classify failed and non-failed corporations. The results show that respondents are most efficient when they classify ac counting Information using Chemoffs schematic faces than any forms o f conven tional accounting information. The effectiveness o f Chemoffs schematic faces is also evidenced when compared to other forms o f accounting information presentation.